Propuesta educativo- pastoral, a partir de la experiencia de Jesús, para la educación para la fe, de los estudiantes de 1º curso de Bachillerato General Unificado (B.G.U) de la Unidad Educativa “P. José María Vélaz, S. J”, ubicado en el sector “El Camal” en Quito”. - Gamboa Quisphe, Ítalo Javier (2013)
The research for this paper was made in order to answer the question of how the development of pedagogy based on the way of teaching of Jesus, Master, achieve meaningful learning in class education for faith, students in Course 1 Unified General Baccalaureate Education Unit "P. José María Vélaz ". Therefore, this paper is structured in the following order: In the first chapter gives an approach to understand the title more often referred to Jesus, the Master, and then respond to what it was like to be a teacher in Jesus, and also where Jesus was formed, the novelty of their teaching and the way of discipleship and monitoring him.